(untitled) (Global Journal of Human-Social Science, 2022)
The purpose of this research was to determine if a correlation exists between video game genres and learning style preferences. The framework used was the cognitive behavioral theoretical framework. The quantitative research that guided the study was the relationship between learning style preference and an individual’s preferred genre of video game. A VARK Survey was implemented to collect data; the second data collection process was the different video game genres people play. The data was analyzed using the Chi-square test of independence. For most video game genres and learning style preferences there was no correlation. Teachers, administration, and workshop educators might benefit by learning how to integrate video game genres to differentiate the lessons for their students.